Structural, Vibrational and Physical Properties on Tetramethyammonium Cadmium Bromide Ferroelectric Single Crystal - Bhuvaneswari, N.; Venkatachalam, K. (Asian Journal of Chemistry, 2017)
Ferroelectric crystals of tetramethylammonium cadmium bromide (TMACB) has been grown by slow evaporation solution growth technique at room temperature. Single crystal X-ray diffraction analysis revealed the newness of the crystal structure belonging to the hexagonal crystal system with lattice parameters a = 9.257 Å, c = 6.9167 Å and a = b = 90º, g = 120º. The functional groups in the complex were identified using FT-IR and FT-Raman analyses. The thermal stability and decomposition details were studied through TG/DTA analyses. The grown crystal was subjected to surface morphology by SEM analysis and the optical properties was studied by UV-VIS-NIR analysis. From the photoluminescence studies, it was confirmed that the grown crystal has been green emission. The Vickers microhardness test conducted on the grown crystal suggests that the crystal has a relatively low mechanical strength. The dielectric constant and dielectric loss were calculated by varying the frequencies at room temperature. Dielectric studies of the grown crystal had been measured in the temperature range of 313 to 453 K.